A novel dielectric elastomer membrane actuator concept for high-force applications. (September 2018) - Hau, S.; Rizzello, G.; Seelecke, S.
Abstract: Dielectric elastomer actuators (DEAs) are known to be lightweight, energy efficient, and scalable in performance. Two well-studied DEA concepts are represented by stacked and membrane DEAs, respectively. The first configuration is known for providing high forces, while the second one results in high strokes. This work proposes a novel design solution, which combines the advantages of both concepts, i.e., high force and stroke, based on a stack of high stroke (3 mm) membrane DEAs. While a single silicone-based DE membrane provides an actuation force on the order of hundreds of mN only, the proposed stacking results into a parallel mechanical connection, which increases the overall force to the double-digit newton range. The biasing mechanism, which is necessary to operate the dielectric elastomer membrane as an actuator, is placed within the passive frame of the DEAs, leading to an overall compact design. To demonstrate the potential of the concept, two prototypes capable of generating record high forces are assembled and tested. The first one allows to lift a weight of 10 kg up to 3 mm, while the second one allows to generate a compression force of 87 N, while working compressing a linear spring with a stiffness of 30.7 N mm −1 up to 2.8mm. These prototypes allow to establish a boosting factor of about 200 for the force output of membrane DEAs.